Constitutive activity of 5-HT receptors: Factual analysis. (15th May 2020) - De Deurwaerdère, Philippe; Bharatiya, Rahul; Chagraoui, Abdeslam; Di Giovanni, Giuseppe
Abstract: The constitutive activity of different serotonin receptors (5-HTRs) toward intracellular signaling pathways has been proposed to have physiological and pathological importance. Inverse agonists block the constitutive activity and can be used to probe and silence such a spontaneous activity. The constitutive activity of 5-HTRs can be observed in various heterologous systems of expression in vitro (very high for 5-HT2C R; very low for 5-HT2A R). The demonstration of the existence of this activity in native tissues and ultimately in integrative neurobiology and behavior is a real pharmacological challenge. Irrespective of the existence of mutants or polymorphisms that could alter the constitutive activity of 5-HTRs, evidence suggests that spontaneous activity of 5-HT2C R could impact the activity of neurobiological networks and that of 5-HT6 R and 5-HT7 R the developmental morphogenesis. Some findings exist for 5-HT2B R and 5-HT2A R in diverse though rare conditions. The existence of a constitutive activity for 5-HT1A R, 5-HT1B/1D R, and 5-HT4 R is still poorly supported. When identified, the constitutive activity may differ according to brain location, state of activity (phasic in nature), and intracellular signaling pathways. A very few studies have reported aberrant constitutive activity of 5-HTRs in animal models of human diseases and patients. The purpose of this review is a critical examination of the available neuropharmacological data on the constitutive activity of 5-HTRs to determine whether this activity is an essential component of the serotonergic system transmission and it may be a possible target for CNS drug development. Highlights: High expression of serotonergic receptors (5-HTR) in transfected cells leads to constitutive activity. The degree of constitutive activity of 5-HTR varies according to the subtype considered in transfected cells. Inverse agonist and antagonist profiles are poorly defined for some 5-HTR subtypes. 5-HT2C R, 5-HT6 R, and 5-HT7 R possibly exhibit constitutive activity in the CNS of mammals. Pathophysiological conditions can be associated with changes in the constitutive activity of some 5-HTR.